2017
DOI: 10.1124/dmd.116.073601
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital Treatment at a Neonatal Age Results in Decreased Efficacy of Omeprazole in Adult Mice

Abstract: Drug-drug interactions (DDIs) occur when the action of one drug interferes with or alters the activity of another drug taken concomitantly. This can lead to decreased drug efficacy or increased toxicity. Because of DDIs, physicians in the clinical practice attempt to avoid potential interactions when multiple drugs are coadministrated; however, there is still a large knowledge gap in understanding how drugs taken in the past can contribute to DDIs in the future. The goal of this study was to investigate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A similar phenomenon on long-term impact of CYP expression by neonatal exposure to drugs has also been observed in mice in later studies (Tien et al, 2015(Tien et al, , 2017Piekos et al, 2018).…”
Section: Impact Of Drug Treatment At Neonatal Ages On Intraindividual...supporting
confidence: 76%
See 1 more Smart Citation
“…A similar phenomenon on long-term impact of CYP expression by neonatal exposure to drugs has also been observed in mice in later studies (Tien et al, 2015(Tien et al, , 2017Piekos et al, 2018).…”
Section: Impact Of Drug Treatment At Neonatal Ages On Intraindividual...supporting
confidence: 76%
“…When mice were older than the age window, no matter how high doses were used, exposure to phenobarbital couldn't cause long-term induction of CYP expression. Phenobarbital treatment at a neonatal age can also result in decreased efficacy in acid suppression in adult mouse stomach by omeprazole, a proton pump inhibitor drug, due to increased metabolism of omeprazole by induced CYP enzymes (Tien et al, 2017). Omeprazole is known to be metabolized by CYP enzymes, mainly by CYP2C19 and 3A4 in human liver (Ishizaki et al, 1999).…”
Section: Impact Of Drug Treatment At Neonatal Ages On Intraindividual...mentioning
confidence: 99%
“…Previous work has shown that direct activation using 1,4-bis[2-(3,5-dichloropyridoyloxy)] benzene, a murine-specific CAR ligand, at the neonatal age also produces permanent alterations to P450 expression (Li et al, 2016a) and function in adulthood, which alters the efficacy of zoxazolamine administered later in life (Chen et al, 2012). Phenobarbital exposure at the neonatal age also caused a decrease in efficacy of omeprazole administered to adult mice, suggesting its role in a possible nonconventional DDI (Tien et al, 2017). Due to phenytoin's ability to cause CAR activation, we presumed that neonatal exposure would also cause a similar permanent alteration to represents GAPDH expression set to 1 (n = 4-6).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the capacity for enzymatic induction varies at different ages during postnatal liver maturation is also not understood. Several studies have additionally suggested neonatal exposures to inducer drugs, particularly the antiepileptic drug (AED) phenobarbital, can cause permanent alterations to expression and activities of P450s in adult rodents Shapiro, 1996, 2005;Tien et al, 2015Tien et al, , 2017Piekos et al, 2017). There also appears to be a window of sensitivity during neonatal life that allows the imprinting of lasting changes to P450 expression following treatment (Tien et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism. The latest literature suggests that persistent epigenetic changes in the promoters of CAR target genes, including Cyp2b10, are responsible for prolonged induction within the F0 generation in the liver (Chen et al, 2012;Peng and Zhong, 2015;Tien et al, 2015Tien et al, , 2017Li et al, 2016;Piekos et al, 2017;Lodato et al, 2018). Our work indicates that at least some of these effects may have been driven by activator accumulation rather than by stable DNA modifications.…”
Section: Soft Inheritance Of Hepatic Inductionmentioning
confidence: 61%